Factors associated with low birth weight among newborns in an urban slum community in Bhopal - A K Choudhary; Asha Choudhary; S C Tiwari; R Dwivedi (Wolters Kluwer Medknow Publications, 2013)
A community based cohort study on birth weight of newborns was conducted among pregnant women of an urban slum in Bhupal, India. The study was carried out to assess the magnitude of low birth weight (LBW) and factors contributing it in an urban slum community. Socio-demographic and maternal characteristics were examined applying statistical techniques to find out the variables associated with the LBW. An additional schedule was used to collect information from mothers about their socio-demographic background, dietary intake and the rest during the pregnancy. Weight of newborns of mothers registered in the study and delivering at the district hospital was recorded. Mean birth weight of newborns of 290 registered mothers was 2.57 ± 0.36 g. One hundred and five newborns (36.2%) had a birth weight lesser than 2500 g. Among different variables studied, statistically significant association was found in case of occupation, daily calorie intake and duration of day-time rest taken by pregnant women.